Analisis Performansi Dan Efisiensi Cloud Computing Pada Sistem Perbankan - Kurniawan, Ketut Adi; Putra Sastra, N; Sudarma, M (Majalah Ilmiah Teknologi Elektro; Vol 19 No 1 (2020): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2020)
The use of physical server for Bank Mandiri branch office operations has several shortcomings, namely the high server procurement costs, limited part upgrading, maintenance costs, land requirements and electricity consumption. An alternative that can be used is cloud computing technology based on virtualization with the ROCCA adoption method. In this research, cloud computing is implemented to run the operational applications of Bank Mandiri branch offices using Microsoft Hyper-V virtualization. Then the performance and value of cost efficiency are compared to the physical server. Implementation results indicate the ROCCA method can be used for cloud computing adoption in the banking sector. Measurement of physical server performance reaches a score of 36% while the cloud server 9%, physical server memory reaches a score of 35% while the cloud server 50%, and the physical server harddisk reach a score of 48% and cloud server 52%. A higher percentage indicates better performance. Regarding to network speed, the physical server reaches a bandwidth of 94.9 Mbits / sec, while the cloud server 94.1 Mbits / sec. In terms of investment efficiency is not too significant, where in 5 years the efficiency value is 1.8% and for 10 years it is 2.81%.